Linking Financial Literacy, Fintech and Financial Inclusion in Cameroon’s Mfoundi Division - Takemeyang, Ayuk; Ketuma, Henry Jong; Akpor, Tambi Andison (Law and Economy, 2026)
Purpose: The purpose of this paper is to investigate how financial literacy influences financial inclusion in Cameroon, and whether financial technology (fintech) adoption plays a role in this relationship. Design/Methodology/Approach: The study is based on primary data collected from a sample of 231 respondents using well-structured questionnaire. The study uses a quantitative approach and the purposive random sampling method with the help of a Structural Equation Model (SEM), which is operated with Smart PLS to test a mediation model where fintech adaption mediates the link between financial literacy and inclusion. Findings: The results indicate that financial literacy significantly boosts financial inclusion, with fintech adoption playing a key partial mediator. Practical Implications: Enhancing literacy programs and expanding fintech access can drive inclusion, informing policymakers. Originality/Value: The study highlights fintech’s mediating role in a developing context, offering insights for Africa’s digital financial push.